2019
DOI: 10.1097/md.0000000000016314
|View full text |Cite
|
Sign up to set email alerts
|

Association between ladybird homeobox 1 gene polymorphisms and adolescent idiopathic scoliosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The rs11598564 SNP was located in the 3′-flanking region of the LBX1 gene, and it was also repeatable in the Chinese Han population (Gao et al, 2013 ; Liu et al, 2017 ). Two meta-analyses conducted in East Asian populations also confirmed that the G allele of rs625039 was the risk allele in AIS (Cao et al, 2016 ; Jiang et al, 2019 ). The detail information for the association of rs625039 and rs11598564 with AIS susceptibility are shown in Table 2 .…”
Section: The Association Of Variants Near Lbx1 With Ais Susceptibilitmentioning
confidence: 83%
See 4 more Smart Citations
“…The rs11598564 SNP was located in the 3′-flanking region of the LBX1 gene, and it was also repeatable in the Chinese Han population (Gao et al, 2013 ; Liu et al, 2017 ). Two meta-analyses conducted in East Asian populations also confirmed that the G allele of rs625039 was the risk allele in AIS (Cao et al, 2016 ; Jiang et al, 2019 ). The detail information for the association of rs625039 and rs11598564 with AIS susceptibility are shown in Table 2 .…”
Section: The Association Of Variants Near Lbx1 With Ais Susceptibilitmentioning
confidence: 83%
“…Recently, the association with disease onset for rs678741 was successfully replicated in the Chinese population (Man et al, 2019 ). Two meta-analyses conducted in multi-ethnic populations also confirmed this susceptibility locus in AIS, and the A allele of rs678741 was considered the risk allele (Cao et al, 2016 ; Jiang et al, 2019 ).…”
Section: The Association Of Variants Near Lbx1 With Ais Susceptibilitmentioning
confidence: 94%
See 3 more Smart Citations